Deciphering imprints of impaired memory B-cell maturation in germinal centers of three patients with common variable immunodeficiency - van Schouwenburg, Pauline; Unger, Susanne; Payne, Kathryn J.; Kaiser, Fabian M. P.; Pico-Knijnenburg, Ingrid; Pfeiffer, Jens; Hausmann, Oliver; Friedmann, David; Erbel, Michelle; Seidl, Maximilian; van Zessen, David; Stubbs, Andrew P.; et al. (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID), characterized by recurrent infections, low serum class-switched immunoglobulin isotypes and poor antigen specific antibody responses, comprises a heterogeneous patient population in terms of clinical presentation and underlying etiology. The diagnosis is regularly associated with a severe decrease of germinal center (GC) derived B-cell populations in peripheral blood. However, data from B-cell differentiation within GC is limited. We present a multiplex approach combining histology, flow cytometry and B-cell receptor repertoire analysis of sorted GC B-cell populations allowing the modelling of distinct disturbances in GCs of three CVID patients. Our results reflect pathophysiological heterogeneity underlying the reduced circulating pool of post-GC memory B cells and plasmablasts in the three patients. In patient 1, quantitative and qualitative B-cell development in GCs is relatively normal. In patient 2, irregular shaped GCs are associated with reduced somatic hypermutation (SHM), antigen selection and class-switching, while in patient 3, high SHM, impaired antigen selection and class-switching with large single clones imply increased re-cycling of cells within the irregular shaped GCs. In lymph nodes of patients 2 and 3, only limited numbers of memory B cells and plasma cells are formed. While reduced numbers of circulating post GC B cells is a general phenomenon in CVID, the integrated approach exemplified distinct defects during GC maturation ranging from near normal morphology and function to severe disturbances with different facets of impaired maturation of memory B cells and/or plasma cells. Integrated dissection of disturbed GC B-cell maturation by histology, flowcytometry and BCR repertoire analysis reveals essential steps during memory formation